Graphene‐Based Transparent Conducting Electrodes for High Efficiency Flexible Organic Photovoltaics: Elucidating the Source of the Power Losses. Issue 5 (7th March 2019) - Wang, Xiao; Zhang, Dingdong; Jin, Hui; Poliquit, Beta Zenia; Philippa, Bronson; Nagiri, Ravi Chandra Raju; Subbiah, Jegadesan; Jones, David J.; Ren, Wencai; Du, Jinhong; Burn, Paul L.; Yu, Junsheng
Abstract : Solution processed flexible organic solar cells (OSCs) are of interest due to their potential use as environmentally friendly, shapeable, or wearable energy. Such flexible devices require compatible transparent conducting electrodes (TCEs). The use of three‐layer graphene as a useful TCE for flexible OSCs is reported. The conformal coating of the graphene‐based TCE with good retention of performance was achieved using a bulk heterojunction (BHJ) active layer comprised of the non‐polymeric molecular (5 Z, 5′ Z )‐5, 5′‐[(5‴, 5‴‴′‐4, 8‐bis[5‐(2‐ethylhexyl)‐4‐ n ‐hexylthiophen‐2‐yl]benzo[1, 2‐b:4, 5‐b′]dithiophene‐2, 6‐diylbis3′, 3″, 3‴‐tri‐ n ‐hexyl‐[2, 2′:5′, 2″:5″, 2‴‐quaterthiophene]‐5‴, 5‐diyl)bis(methanylylidene)]bis[3 ‐n ‐hexyl‐2‐thioxothiazolidin‐4‐one] (BQR) donor and [6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PC71 BM) as the acceptor. This material combination enables thick BHJ junctions to be used so that the roughness of the graphene surface did not lead to shorted devices. The best graphene/poly(ethylene terephthalate) (PET) devices (PET/graphene/molybdenum oxide/BHJ/calcium/aluminum) show a photoconversion efficiency (PCE) of 5.8%, which while excellent was lower than that of a similar device architecture that used ITO/glass as the anode. The power losses of the graphene/PET‐based cells mainly resulted from absorption losses caused by the optical profile distribution in the device and the relatively high sheet resistance of the anode, leading to an 18% decrease in the short‐circuit current and lower fill factor, respectively. Abstract : Three‐layer graphene is used as the transparent conducting electrode for flexible organic solar cells . A thick bulk heterojunction active layer comprised of a blend of the non‐polymeric molecular donor BQR and PC71 BM enables coverage of the rough graphene surface so as to avoid shorted devices. The best devices (PET/graphene/molybdenum oxide/BHJ/calcium/aluminum) have a photoconversion efficiency of 5.8%.